2019
DOI: 10.1186/s12978-019-0721-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing men’s involvement in antenatal care services: a cross-sectional study in a low resource setting, Central Tanzania

Abstract: Background Men’s involvement can impact the delays in the decision to seek health care and in reaching a health facility, which are contributing causes for increased maternal mortality. Despite of the call to involve men in antenatal care, their participation is not well understood. This study aimed to determine the level of men’s involvement in antenatal care and the factors influencing their involvement in these services. Methods A cross sectional study of 966 randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
46
3
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 36 publications
14
46
3
4
Order By: Relevance
“…This study showed that the man accompanying his wife to the health facility for the ANC service is low. The ndings are consistent with the results of studies conducted in Ghana (35%) (8) But the results are higher than a study conducted in Nigeria (24%) (10); and lower than studies conducted in Eastern Ethiopia (45.2%), Tanzania (63.4%) and Myanmar (82%) (11)(12)(13), respectively. This may be due to differences in socio-cultural and health care environments.…”
Section: Discussionsupporting
confidence: 87%
“…This study showed that the man accompanying his wife to the health facility for the ANC service is low. The ndings are consistent with the results of studies conducted in Ghana (35%) (8) But the results are higher than a study conducted in Nigeria (24%) (10); and lower than studies conducted in Eastern Ethiopia (45.2%), Tanzania (63.4%) and Myanmar (82%) (11)(12)(13), respectively. This may be due to differences in socio-cultural and health care environments.…”
Section: Discussionsupporting
confidence: 87%
“…This is evident from our participants' mixed views on condoms, and how some felt they could not continue having sexual relations with their partners if they must use condoms, with others viewing it as a preventive measure and some not being sure it was the right thing for them. Health promotion outside of ANC is therefore needed to empower men with essential information for meaningful involvement [29]. Our ndings support the conclusions of Kura et al [22], who report that inadequate knowledge, cultural factors and lack of appropriate services adversely affect men's involvement in their wives and their own sexual and reproductive health.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, the historic institutionalisation of reproductive health, and particularly maternal health, as a women-only realm has yielded health services that continue to not accommodate men, contributing to men's perception of clinic spaces as 'women's spaces' and reproductive health as 'women's health' [15,27,28]. This study concurs that the traditional emphasis on maternal health has resulted in men being neglected in much of the sexual and reproductive health education [10,29].…”
Section: Discussionsupporting
confidence: 60%
“…Only a small portion of husbands (35.8%) provided a high level of support in maternal health. This finding was lower than others [17][18][19][20]. For example, in a study in rural Bangladesh, Rahman et al [17] found that 47% of women who attended an ANC visit were accompanied by their husbands and approximately half of the husbands were present at the time of childbirth while 67% were with their wives during a PNC visit.…”
Section: Discussionmentioning
confidence: 86%